Differential avidity determination of IgG directed towards the receptor‐binding domain (RBD) of SARS‐CoV‐2 wild‐type and its variants in one assay: Rational tool for the assessment of protective immunity. Issue 11 (26th July 2022) - Bauer, Georg; Struck, Friedhelm; Staschik, Eva; Maile, Julia; Wochinz‐Richter, Karin; Motz, Manfred; Soutschek, Erwin
Abstract: The avidity (binding strength) of IgG directed towards the receptor‐binding domain (RBD) of spike protein has been recognized as a central marker in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) serology. It seems to be linked to increased infection‐neutralization potential and therefore might indicate protective immunity. Using a prototype line assay based on the established recomLine SARS‐CoV‐2 assay, supplemented with RBD of the delta and the omicron variant, differential avidity determination of IgG directed towards RBD of wild‐type (WT) SARS‐CoV‐2 and distinct variants was possible within one assay. Our data confirm that natural SARS‐CoV‐2 infection or one vaccination step lead to low avidity IgG, whereas further vaccination steps gradually increase avidity to high values. High avidity is not reached by infection alone. After infection with WT SARS‐CoV‐2 or vaccination based on mRNA WT, the avidity of cross‐reacting IgG directed towards RBD of the delta variant only showed marginal differences compared to IgG directed towards RBD WT. In contrast, the avidity of IgG cross‐reacting with RBD of the omicron variant was always much lower than for IgG RBD WT, except after the third vaccination step. Therefore, parallel avidity testing of RBD WT and omicron seems to be mandatory for a significant assessment of protective immunity towards SARS‐CoV‐2.